Congestion pricing practices and public acceptance: A review of evidence. Issue 1 (March 2018) - Gu, Ziyuan; Liu, Zhiyuan; Cheng, Qixiu; Saberi, Meead
Highlights: A trial and a referendum are valuable but not necessary for the successful implementation of congestion pricing. An interaction-oriented political process is advisable to ensure information sharing between government and the public. Privacy, equity, complexity, and uncertainty are four factors influencing public acceptance toward congestion pricing. An extended three-step approach is proposed for improving public acceptance toward congestion pricing. Abstract: Despite numerous theoretical studies, practical implementation of congestion pricing is limited mainly due to the low public acceptance. Existing studies in this respect generally focus on a few selected cases where the results need to be further generalized. With the objective of improving public acceptance of congestion pricing, this paper provides a comprehensive overview of the area-based congestion pricing practices. An in-depth analysis of public acceptance is presented using a qualitative case study approach. Results show that for the successful implementation of congestion pricing, a trial and a referendum are valuable but not necessary, and that an interaction-oriented political process may be more desirable. Four influencing factors, i.e. privacy, equity, complexity and uncertainty, are identified to be critical in establishing strong public support. Taking into account these implementation factors, an extended three-step approach is proposed for further improvement of public acceptance toward congestion pricing.